Prototheca species and Pithomyces chartarum as Causative Agents of Rhinitis and/or Sinusitis in Horses. Issue 2 (August 2016) - Schöniger, S.; Roschanski, N.; Rösler, U.; Vidovic, A.; Nowak, M.; Dietz, O.; Wittenbrink, M.M.; Schoon, H.-A.
Summary: Pyogranulomatous rhinitis associated with an algal infection was diagnosed in a 25-year-old gelding and a 23-year-old mare had necrotizing sinusitis with intralesional algae and pigmented fungi. Algae were identified immunohistochemically in both cases as Prototheca spp. In the gelding, further characterization by polymerase chain reaction and sequencing revealed that the organism was Prototheca zopfii genotype 2. Fungi from the mare were identified as Pithomyces chartarum by molecular analysis. Prototheca species are achlorophyllous algae and P. chartarum represents a dematiaceous fungus; they are saprophytes and facultative pathogens. Prototheca spp. and P. chartarum should be considered as rare respiratory pathogens of horses.